Outcome evaluation of Active Herts: A community-based physical activity programme for inactive adults at risk of cardiovascular disease and/or low mental wellbeing - Chater, Angel M.; Schulz, Joerg; Jones, Andy; Burke, Amanda; Carr, Shelby; Kukucska, Dora; Troop, Nick; Trivedi, Daksha; Howlett, Neil (Frontiers in public health, 2022)
A high proportion of UK adults are inactive, which can lead to a range of physical and mental health concerns. Active Herts is a community-based physical activity programme for inactive adults at risk of cardiovascular disease and/or low mental wellbeing. This paper provides a pragmatic evaluation of this programme. This longitudinal study observed 717 adults (68% female, mean age = 56.9 years) from the "Active Herts" programme. Programme users were provided with a 45-min consultation with a "Get Active Specialist," who talked them through an Active Herts self-help booklet and then signposted them to free or subsidized local exercise sessions. Programme users were followed up with a booster call 2 weeks later. The Get Active Specialist was a registered exercise professional (REPS Level 3), with additional training from the study team in motivational interviewing, health coaching, COM-B behavioral diagnosis and delivery of behavior change techniques (BCTs) in practice. The Active Herts booklet contained theoretically-driven and evidence-based BCTs to translate behavioral science into public health practice. Physical activity (Metabolic Equivalent Time [METs], measured using the International Physical Activity Questionnaire (IPAQ), perceived health (EQ-5D-5L) and mental wellbeing (Warwick-Edinburgh Mental Wellbeing Scale: WEMWBS) were measured at baseline, 3, 6 and 12 months. At the end of the 12-month programme, users showed sustained improvements in physical activity (by +1331 METS), exceeding weekly recommendations. Sitting (reducing by over an hour per day), sporting participation, and perceptions of health were also improved, with improvements in mental wellbeing in the first 3 months. Designing and delivering a community-based physical activity programme that is theoretically-driven and evidence-based with frequent behavior change training and supervision can yield a significant increase in self-reported physical activity, reduction in sitting behavior and improvements to perceived health and mental wellbeing. Future research should extend this approach, utilizing a real-world, pragmatic evaluation. ClinicalTrials.gov, identifier (NCT number): NCT03153098.